(untitled) (Revista de Artes Marciales Asiáticas, 2025)
Wushu, commonly known as kung-fu, is a demanding sport requiring rapid force application to achieve significant vertical jump heights. These jumps are integral for executing complex aerial tasks and obtaining higher performance scores. Purpose: This study aimed to establish normative data for countermovement jump (CMJ) performance parameters in elite wushu athletes. Methods: A cross-sectional design was implemented at the 2022 Malaysia Games (SUKMA) wushu competition with 115 athletes (males=67). Each athlete performed three CMJs with hands akimbo on a pair of force platforms. Performance and biomechanical data (vertical jump height, peak relative propulsive power, peak relative propulsive force, modified reactive strength index, and relative propulsive net impulse) were collected using Hawkins Dynamics software. An ANCOVA was used to compare CMJ parameters across sex and events, controlling for age and body mass. Normative data were established using t-scores. Results: The ANCOVA indicated that CMJ and biomechanical variables differed by sex and age (p<0.01), but not by event. Conclusion: These normative values provide a baseline for understanding CMJ performance in elite wushu athletes and may guide further exploration of training adaptations, injury risk assessment, and performance optimization. However, additional research is warranted to fully validate and expand on the potential practical applications of these findings.